2020
DOI: 10.1097/rli.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentric Comparison of Apparent Diffusion Coefficient Mapping and the Kaiser Score in the Assessment of Breast Lesions

Abstract: Objective: We sought to compare the diagnostic performance of apparent diffusion coefficient (ADC) mapping with the Kaiser score (KS) to distinguish benign from malignant breast lesions and to assess the potential of this approach to help avoid unnecessary biopsies. Materials and Methods: In this multicentric study, individual patient data from 3 different centers were analyzed. Consecutive patients receiving standardized multiparametric breast magnetic resonance imaging for standard nonscreening indications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
4
35
0
7
Order By: Relevance
“…More critical evaluation will be considered in follow-up work, including studying as many systems, protocols, and centers as we possibly can. Analogous to Dietzel et al (10), our results showed that the sensitivity with Kaiser score+ also decreased. The missed lesion was a rare finding that exhibited atypical morphological patterns of a malignant lesion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More critical evaluation will be considered in follow-up work, including studying as many systems, protocols, and centers as we possibly can. Analogous to Dietzel et al (10), our results showed that the sensitivity with Kaiser score+ also decreased. The missed lesion was a rare finding that exhibited atypical morphological patterns of a malignant lesion.…”
Section: Discussionsupporting
confidence: 89%
“…As a clinical decision rule, Kaiser score (a clinical scoring system) incorporating several BI-RADS diagnostic criteria has demonstrated robust performance in the assessment of breast lesions with excellent sensitivity and specificity (8)(9)(10)(11)(12)(13), which could potentially avoid unnecessary biopsies. The Kaiser score consists of 11 rating categories ranging from 1 to 11, with each category corresponding to a distinct likelihood of malignancy (13).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with prior reports applying the same score in high-risk patients [17], lesions presenting as mammographic microcalcifications [18] and suspicious BI-RADS 4 lesions only visible on MRI [19]. Notably, according to a multicentric analysis, the Kaiser score seems to be better suited to this task than the most promising quantitative imaging biomarker in breast imaging, the Apparent Diffusion Coefficient derived from Diffusion Weighted Imaging [20]. These findings suggest the clinical application of the Kaiser score as an effective tool to avoid unnecessary biopsies at a high level of evidence.…”
Section: Avoiding Unnecessary Biopsiessupporting
confidence: 88%
“…The interobserver agreement for the Kaiser score varied between the earlier studies, ranging from fair to almost perfect agreement [14,15,[17][18][19]22]. This indicates that, while the Kaiser score is simple and easy to use, there may be some challenging aspects.…”
Section: Discussionmentioning
confidence: 91%